Discovering Skin Anti-Aging Potentials of the Most Abundant Flavone Phytochemical Compound Reported in Siam Violet Pearl, a Medicinal Plant from Thailand by In Silico and In Vitro Assessments - Chaiyawat Aonsri; Sompop Kuljarusnont; Duangjai Tungmunnithum (Antioxidants)
Currently, nutraceuticals and functional food/cosmeceutical sectors are seeking natural molecules to develop various types of phytopharmaceutical products. Flavonoids have been reported in antioxidant and many medical/pharmacological activities. Monochoria angustifolia or Siam violet pearl medicinal plant is the newest species of the genus Monochoria C. Presl, which have long been consumed as food and herbal medicines. Though previous work showed that apigenin-7-O-glucoside is the most abundant antioxidant phytochemical found in this medicinal plant, the report on anti-aging activity is still lacking and needs to be filled in. The objective of this work is to explore anti-aging capacities of the most abundant antioxidant phytochemical reported in this plant using both in silico and in vitro assessments. In addition, pharmacokinetic properties were predicted. Interestingly, the results from both in silico and in vitro analysis showed a similar trend that apigenin-7-O-glucoside is a potential anti-aging agent against three enzymes. The pharmacokinetic properties, such as adsorption, distribution, metabolism, excretion and toxicity (ADMET), of this compound are also provided in this work. The current study is also the first report on anti-aging properties of this Thai medicinal plant. However, the safety and efficacy of future developed products from this compound and clinical study should be determined in the future.